SUPPLY AND DEMAND ANALYSIS OF BURUNG BATU BEACH TOURISM OBJECT IN SINGKAWANG, WEST KALIMANTAN - Erni, Yuniarti; Indah, Fitriani Meta; Iman, Sumantri; B, Soeryamassoeka S; R, Hernovianty F (Fakultas Teknik Universitas Tanjungpura, 2022)
Singkawang City West Kalimantan Province has one of the natural attractions of the beach is Batu Burung Beach. The attraction of this object is the panorama of the beach with granite stones which is based on the history as the gathering place of birds. The attraction of Batu Burung Beach has not been the main destination for tourists, because it has not been developed properly and realized optimally. The factor that hinders the development of tourist attractions is marketing so that not many tourists know about the existence of this attraction. This research purposed to analyse the potential of supply and demand tourist attractions Batu Burung Beach. The research method used is quantitative method and supported by qualitative method. The analysis method that used to analyse potential supplies is ODTWA analysis, while to analyse potential demands is using descriptive analysis. The results of research on Batu Burung Beach attractions show that it is worth developing as a beach tourist destination. Based on the recapitulation of the value of potential objects and tourist attractions, the beach got a potential value index of 77.33% which falls into the category worth to be developed. The criteria that requires follow-up actions so that this object can be in priority scale and developed into a beach tourist attraction is marketing. While the potential demand criteria that require follow-up actions is the need for the expansion of tourist attraction areas, widening of the entrance, procurement of sign boards, the addition of shelters, the expansion of toilets and prayer rooms, the addition of food stalls, and the procurement of social media and information brochures. Batu Burung Beach tourism object with this handling is expected to be developed into an alternative beach tourist destination in Singkawang City.